2019
DOI: 10.12998/wjcc.v7.i15.2065
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas therapy induced shrinkage of metastatic gallbladder cancer: A case report

Abstract: BACKGROUND We present the case of a 72-year-old female patient with gallbladder cancer (GBC) who developed in situ recurrence and liver metastases 9 mo after irreversible electroporation ablation and oral tegafur (a fluoropyrimidine derivative) chemotherapy, which failed to control the progression of the disease. The patient further developed metastases in the lymph nodes around the head of the pancreas. The patient had severe anemia, requiring weekly blood transfusions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Inhalation of H 2 drastically inhibited tumor growth in mouse xenografted with BGC-823 cells (p < 0.01, H 2 vs. Ctrl) (Fig. 7 ), which was consistent with clinical observation of different cancers [ 23 , 25 ]. Overexpression of lncRNA MALAT1 partially suppressed H 2 caused inhibition of tumor growth whereas miR-124-3p counteracted the effect of lncR MALAT1 (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Inhalation of H 2 drastically inhibited tumor growth in mouse xenografted with BGC-823 cells (p < 0.01, H 2 vs. Ctrl) (Fig. 7 ), which was consistent with clinical observation of different cancers [ 23 , 25 ]. Overexpression of lncRNA MALAT1 partially suppressed H 2 caused inhibition of tumor growth whereas miR-124-3p counteracted the effect of lncR MALAT1 (Fig.…”
Section: Resultssupporting
confidence: 86%
“…As hydrogen gas has been shown to inhibit cancer progression [ 25 ] and lung cancer cell proliferation [ 26 ], we first examined whether it could impact the proliferation of gastric cancer cells. After 24 h exposure to hydrogen gas, the viable MGC-803 and BGC-823 cells were reduced more than 20% compared to normally cultured ones (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has revealed that H 2 not only improved the side effects induced by chemotherapeutics, but also inhibited cancer growth (22)(23)(24). In addition, Chen et al (25) reported that H 2 treatment reduced the metastases size in the abdominal cavity, improved anemia and hypoalbuminemia and gradually returned the lymphocyte and tumor marker levels, including CA19-9, α fetoprotein and carcinoembryonic antigen to normal. In our previous study, it was found that H 2 treatment effectively inhibited lung cancer cell growth and induced cell apoptosis by targeting the structural maintenance of chromosomes 3 gene in a dose-dependent manner, with no side effects on the non-tumor burdened mice (6).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhalation of H 2 gas markedly suppressed focal ischemia and reperfusion (I/R)-induced brain injury in rats by buffering the effects of oxidative stress. From then on, researchers have extensively investigated the functions and mechanisms of H 2 , studies indicated that supplement of exogenous H 2 has the potential abilities to protect against acute or chronic damage of tissues or organs, including brain, heart, blood vessel, lung, stomach, intestine, pancreas, liver, gallbladder, kidney, testis, ovary, breast, eye, ear, bones, skin, et al (Guo et al, 2013;Sun et al, 2013;Zhang et al, 2016a;Zhang et al, 2016b;Ge et al, 2017;Zhang et al, 2017;Frajese et al, 2018;Zhang et al, 2018b;Chen et al, 2019;Tan et al, 2019;Tao et al, 2019). H 2 dissolved in medium protected PC12 cells against cell death in a dose-dependent manner, as that H 2 > 25 mM had significant anti-oxidative effect (Ohsawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%